Manajemen Sekolah Digital Melalui Program Smart Classroom (SCR) - Sizka Farwati; Zainal Arifin (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This article explains the implementation of digital school management through the Smart Classroom (SCR) program. This qualitative research approach uses descriptive analysis—data collection techniques through observation, documentation, and in-depth interviews. The study results show that a digital school is an educational institution with a learning process using digital equipment, books, and applications. Digital school management is establishing and implementing IT-based programs through the Smart Classroom program using software and hardware products. Second, Smart Classroom Learning at Al-Azhar 37 Islamic Middle School Pekanbaru uses an iPad. Educators create web-based, Google, and application-based learning materials. They were giving assignments/homework through tests and quizzes. Assessment of exam results through the Google form, students make important notes equipped with photo and video features that can be shared using the notes application as a collaboration with friends. This implementation has received support from the school by facilitating internet access via Wi-Fi hotspots within 24 hours. Third, the urgency of Smart Classrooms in educational institutions will make learning more effective, innovative, fun, comprehensive, and time efficient. The implications of this research are very beneficial for all elements of the school because it can facilitate the current student-centered learning process.